Essential oil composition of endemic Cyclotrichium niveum (Boiss.) Manden & Scheng (Lamiaceae) from Turkey: A chemotoxonomic approach - Dogan, Gulden; Bagci, Eyup (Chemical Publishing Co., 2016)
In this study, hydrodistilled essential oil derived from the aerial parts of Cyclotrichium niveum (Boiss.) Manden. & Scheng (Lamiaceae) grown in Turkey were analyzed by GC and GC-MS system. Fourty seven components were identified representing 94.2 % of the oil. It was determined that C. niveum essential oil contained pulegone (32.0 %), germacrene-D (16.9 %), menthone (16 %), isomenthone (8.8 %) and spathulenol (3.4 %) as major compounds, respectively. Essential oil analysis of the Cyclotrichium niveum has shown that it has pulegone/germacrene-D and menthone chemotype. The results were discussed by using numerical taxonomic clustering techniques in means of chemotaxonomy with the genus patterns. The dendrogram showed that the essential oil composition of Cyclotrichium genus patterns have different content but similar profiles in view of major compounds.
Keywords: Chemotaxonomy; Cyclotrichium niveum; Essential oil; Germacrene-D; Pulegone